Effects of selective distribution and migration of poly(methyl methacrylate)-grafted nanoclays on the phase behavior of poly(methyl methacrylate)/poly (styrene-co-acrylonitrile) blends. (14th June 2022) - Zhang, Xinyue; Zhang, Haimo; Zuo, Min; Zhong, Jun; Shi, Xuanyu; Sun, Shihao; Yang, Li; Song, Yihu; Zheng, Qiang
Abstract: The effect of selective distribution and migration behavior of two kinds of poly (methyl methacrylate)-grafted nanoclays (PMMA- g -clay) on the phase behavior of PMMA/poly (styrene- co -acrylonitrile) (SAN) blends is investigated. The grafting ratios of our two modified nanoclays are similar, but their grafting density and grafted chain lengths are different, resulting in their different initial locations and subsequent migration behaviors in the blend matrix. The PMMA- g -clay(d) nanosheets (NSs) with relatively dense and short chains are always distributed at the interfacial region and further form the percolation networks to block the concentration fluctuation and retard the domain coarsening of blend matrix more remarkably, while the PMMA- g -clay(s) NSs with relatively sparse and long chains are distributed at first in the SAN-rich domains and subsequently move slowly to the interfacial region, resulting in their inhibition of the phase separation for PMMA/SAN blend from retarding SAN chains' viscous diffusion to their gradual interfacial aggregation for stabilizing the morphology. The variation of storage modulus for three systems in low frequency and long-time regimes are also affected by different selective distributions of two grafted clay NSs in PMMA/SAN blend matrix. Graphical abstract: Image 1 Highlights: The compatibilization effects of two clay nanosheets grafted with different length and grafting density of PMMA chains were compared. The two nanosheets have the same thermodynamically stable location but different migration behaviors. Both the two nanosheets hardly affect the phase coarsening of polymer blend at the early stage of the spinodal decomposition. The inhibition effects of the two nanosheets are different at intermedium and late stages.